World Economy Autumn 2022 - Global growth falters - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Nils Sonnenberg; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2022)
In spring 2022, world economic growth came to a standstill amid high inflation, persistent supply bottlenecks and elevated uncertainty. In many countries real wages are declining significantly dampening private consumption even though extra savings accumulated during the pandemic are still available to mitigate the adverse impact to some extent. At the same time financial conditions have also deteriorated as central banks tightened their policies. In China, the strict zero-covid policy and problems in the real estate sector are slowing economic activity. Against this backdrop, the outlook for the global economy has deteriorated further. We have, again, lowered our forecast and are now expecting global output to increase by only 2.9 percent this year and 2.2 percent next year (calculated on a purchasing power parity basis). The forecast assumes that commodity prices will gradually decline in line with forward prices, which will over time reduce the upward pressure on prices and provides the foundations for an economic upturn in 2024. However, the pass-through of higher commodity prices into consumer prices is probably not yet complete and wage increases are likely to intensify in many countries. Consequently, underlying inflation is likely to remain higher than in the years before the Covid crisis and remain above central bank targets over the forecast horizon.
Keywords: 330; advanced economies; emerging economies; monetary policy